Trends in worldwide research on cardiac fibrosis over the period 1989–2022: a bibliometric study - Mao, Yukang; Fu, Qiangqiang; Su, Feng; Zhang, Wenjia; Zhang, Zhong; Zhou, Yimeng; Yang, Chuanxi (Frontiers in Cardiovascular Medicine, 2023)
Background: Cardiac fibrosis is a hallmark of various end-stage cardiovascular diseases (CVDs) and a potent contributor to adverse cardiovascular events. During the past decades, extensive publications on this topic have emerged worldwide, while a bibliometric analysis of the current status and research trends is still lacking. Methods: We retrieved relevant 13,446 articles on cardiac fibrosis published between 1989 and 2022 from the Web of Science Core Collection (WoSCC). Bibliometrix was used for science mapping of the literature, while VOSviewer and CiteSpace were applied to visualize co-authorship, co-citation, co-occurrence, and bibliographic coupling networks. Results: We identified four major research trends: (1) pathophysiological mechanisms; (2) treatment strategies; (3) cardiac fibrosis and related CVDs; (4) early diagnostic methods. The most recent and important research themes such as left ventricular dysfunction, transgenic mice, and matrix metalloproteinase were generated by burst analysis of keywords. The reference with the most citations was a contemporary review summarizing the role of cardiac fibroblasts and fibrogenic molecules in promoting fibrogenesis following myocardial injury. The top 3 most influential countries were the United States, China, and Germany, while the most cited institution was Shanghai Jiao Tong University, followed by Nanjing Medical University and Capital Medical University. Conclusions: The number and impact of global publications on cardiac fibrosis has expanded rapidly over the past 30 years. These results are in favor of paving the way for future research on the pathogenesis, diagnosis, and treatment of cardiac fibrosis.